2014
DOI: 10.1089/neu.2008.0814
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypothermia on the Expression of TIMP-3 after Traumatic Brain Injury in Rats

Abstract: Here we investigate the effect of hypothermia on the expression of apoptosis-regulating protein TIMP-3 after fluid percussion traumatic brain injury (TBI) in rats. We began with 210 adult male Sprague-Dawley rats and randomly assigned them to three groups: TBI with hypothermia treatment (328C), TBI with normothermia (378C), and sham-injured controls. TBI was induced by a fluid percussion TBI device. Mild hypothermia (328C) was achieved by partial immersion in a water bath (08C) under general anesthesia for 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the fluid percussion TBI rat model, it was shown that the apoptosis-regulating protein TIMP-3 increased in normothermic group and reduced in hypothermic group (Jia, et al, 2012). This is consistent with our observation that HPI201 suppresses pro-apoptosis genes and increasing anti-apoptotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the fluid percussion TBI rat model, it was shown that the apoptosis-regulating protein TIMP-3 increased in normothermic group and reduced in hypothermic group (Jia, et al, 2012). This is consistent with our observation that HPI201 suppresses pro-apoptosis genes and increasing anti-apoptotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in humans TIMP-1 levels correlated with increased mortality and served as a possible biomarker for injury severity (Lorente et al, 2014). TIMP-3 is another member of this family that was found to be elevated in both injured and uninjured brain hemispheres after fluid percussion injury in rats - a response that was blocked by mild hypothermia (Jia et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Preliminary achievements have been made regarding the treatment of TBI with hypothermia [20][21][22]; however, the effects of nontherapeutic, uncontrolled hypothermia on TBI are unclear. In the present study, we used a CCI mouse model to simulate TBI in a clinical setting, and LSCI was used to track and observe the changes in cerebral surface venous blood ow and microcirculation and to assess their relationship with cytokines.…”
Section: Discussionmentioning
confidence: 99%